Judicial Constitutional Capture and the Transformation of Democratic Backsliding in Indonesia - Exsyel Hendy Basuki; Windya Nopryanti; Hezron Sabar Rotua Tinambunan; Mohammed Ali Ahmed Saeed (Unnes Law Journal, 2026)
This article examines whether the Indonesian Constitutional Court's Decision No. 90/PUU-XXI/2023 should be understood as ordinary constitutional adjudication or as a distinct form of democratic backsliding. Using qualitative-normative legal research, critical doctrinal analysis, precedent tracking, and functional comparative comparison, it analyzes the Court's treatment of standing, open legal policy, conditional constitutionality, plurality reasoning, judicial ethics, and electoral timing. The article argues that Decision No. 90 represents judicial constitutional capture: an endogenous pathology in which a constitutional court becomes an autonomous agent of constitutional manipulation rather than merely a victim of executive capture or a passive validator of political power. The finding rests on the convergence of weak proxy-like standing, abrupt departure from same-cycle precedents, a fractured majority whose broad remedy lacked clear majority reasoning, judicial positive legislation, an objective familial conflict of interest, and subsequent Ethics Council findings. The article contributes a litmus test distinguishing aggressive judicial activism from capture and proposes reforms concerning preventive recusal, heightened standing in election-rule cases, supermajority requirements for departing from recent precedent, plurality-ratio rules, targeted cooling-off safeguards, and stronger ethics sanctions. It concludes that constitutional courts require internal integrity mechanisms as much as external independence protections.